PENGARUH REPUTASI DAN KUALITAS INFORMASI YANG DIMEDIASI OLEH KEPERCAYAAN TERHADAP MINAT BELI PADA PENGGUNA SHOPEE DI KOTA BANDA ACEH - Rizqullah Rizqullah; Syarifah Evi Zuhra (Departemen Manajemen, 2021)
This study aims to measure the effect of Reputation and Quality Information on Purchase Intention mediated by Trust at Shopee‟s buyers in Banda Aceh City. The sample used in this study were customers of Shopee in Banda Aceh City, amounting to 150 respondents. Data collection equipment used in this study is a questionnaire. The sampling technique used is nonprobability sampling and purposive sampling. Hierarchical Linear Modelling (HLM) is used as an analytical method to determine the effect of the variables involved. Based on the results of HLM that reputation has a significant effect on trust, Quality information has a significant effect on trust, Reputation has a significant effect on purchase intention, Quality information has a significant effect on purchase intention, Trust has a significant effect on purchase intention, Trust mediates the effect of reputation on purchase intention and trust mediates the effect of quality information on purchase intemtion